Influence of Managerial Skills on Completion of PPP Projects: A Case of Sondu-Miriu Power Project in Kenya - Pamela Oyieyo; Charles Rambo; Anne Ndiritu (International Journal of Management, Accounting and Economics, 2020)
PPP projects are aimed at finding solutions to public problems by taking advantage of resources in the hands of public sector by combining the strengths in public and private sectors to solve problems that members of public face. The purpose of this study was to assess the Influence of Managerial Skills on Completion of PPP Projects: A Case of Sondu-Miriu Power Project in Kenya. The researcher adopted a correlational design where purposive sampling technique was adopted to select 39 management staff who were administered with questionnaires face to face or by mail. Mean and standard deviation were used for descriptive analysis while Pearson correlation was used for inferential purposes. The study found that delegating work to people with time to complete tasks moderately improves on completion of PPP projects. Further, following up on team members whose behaviors might impact projects negatively highly improves completion of PPP projects in terms of quality, time and cost. The study concludes that managerial skills strongly positively influence completion of PPP projects. The study recommends that, during implementation of PPP, selection of managers should be critically done to ensure that candidates with proven records and abilities are selected to implement the project.